Changing to Daylight Saving Time Cuts into Sleep and Increases Workplace Injuries - Barnes, Christopher M. (Institutional Knowledge at Singapore Management University, 2009)
The authors examine the differential influence of time changes associated with Daylight Saving Time on sleep quantity and associated workplace injuries. In Study 1, the authors used a National Institute for Occupational Safety and Health database of mining injuries for the years 1983–2006, and they found that in comparison with other days, on Mondays directly following the switch to Daylight Saving Time—in which 1 hr is lost—workers sustain more workplace injuries and injuries of greater severity. In Study 2, the authors used a Bureau of Labor Statistics database of time use for the years 2003–2006, and they found indirect evidence for the mediating role of sleep in the Daylight Saving Time–injuries relationship, showing that on Mondays directly following the switch to Daylight Saving Time, workers sleep on average 40 min less than on other days. On Mondays directly following the switch to Standard Time—in which 1 hr is gained—there are no significant differences in sleep, injury quantity, or injury severity.